Helmholtz Illusion Makes you Look Fit Only When you are Already Fit, But not for Everyone. (August 2013) - Ashida, Hiroshi; Kuraguchi, Kana; Miyoshi, Kiyofumi
A square filled with horizontal stripes is perceived as thinner than one with vertical stripes (Helmholtz illusion). This is not consistent with a common belief that horizontally striped clothing makes a person look fatter, and studies on this problem have shown inconsistent results. Here, we demonstrate three factors that could have complicated the issue. First, the Helmholtz effect is stronger for a thin figure than for a fat one, with possible reversal for the latter. Second, we found large variability across participants, suggesting dependence on features to attend. Third, there was strong hysteresis as to the order of testing fat and thin figures, suggesting the effect of surrounding people in daily life. There can be yet other factors, but we should note that this apparently simple case of application of a geometrical illusion in daily perception should be taken as a rather complex phenomenon.